Uncertainty Reduction Theory in a New Work Environment: A Case of Teachers and School Principals Mutation in Cilandak District - Vusparatih, Dina Sekar (Humaniora, 2019)
This researched aimed to show the mutation in the education field in Indonesia because every teacher and principal would have at least once in his/her carrier. Through a qualitative approach and a case study method in Cilandak subdistrict, this research tried to analyze how educators underwent mutations using strategies from Uncertainty Reduction Theory (URT). By using interview and observation techniques, it is found that almost all educators use passive, active, and interactive strategies in gathering various information about the new school that is intended before carrying out the transfer. A forum of teachers or principals and joining community educator groups can be a bridge and media in carrying out this strategy so that it can reduce uncertainties in facing new environments and avoid conflicts that may occur due to ignorance and other threats. To get a certain situation using URT, it needs good competence in interpersonal communication as well.